Балади та Біблія - Мак-Карті, В. (Народна творчість та етнологія, 2012)
William McCarthy. Ballads and the Bible. The Hebrew Bible (Old Testament) attests to the rich oral tradition of the Hebrew people. It contains a book of traditional religious songs in the Psalms, a book of Proverbs, a book of origin myths called Genesis, and even a book of heroic tales, Judges. But it does not contain a book of ballads. It does, nevertheless, include two songs that seem to function as historical ballads, the Song of Moses (Exodus 15) and the Song of Deborah (Judges 5). In each case, the song or ballad seems to be one of the sources for the preceding prose narrative of events also covered in the song. The earlier books of the Bible, concerned (at least in part) with preserving historical and legendary traditions, are full of tags of song used to amplify the narrative. The prophets also seem to have known a ballad tradition and to have drawn upon it in interesting ways. The poetry of the prophets contains images and especially rhetorical figures that echo the imagery and rhetoric of the Song of Deborah in particular, suggesting that ballad diction was one of the resources that prophets drew upon in fashioning their utterances.